Assessment of knowledge, attitude and practice towards fluorides and fluorosis among rural people in fluoride endemic region of Kondagaon, Central India - Jewel, Jonathan Vinay; Dhruw, Sonal; Roy, Pritam Kumar; Pydipalli, Mounika; Dixit, Anand; Maurya, Pradeep Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: Fluoride has advantages but acts as a toxin if consumed in excess. It interferes with the normal process of enamel as well as bone formation leading to an increased risk of dental and skeletal fluorosis. This study was aimed to assess the knowledge, attitude and practices related to fluoride and fluorosis among the residents of fluoride endemic villages of Kondagaon, Central India. Methods: The study was carried out among 600 individuals aged 5 years and above. Each village was considered as a cluster. The number of participants from each village was determined based on proportionate sampling following which households in each village were selected based on systematic random sampling. Results: Among the participants one-fourth of the total participants (26%) had heard the term fluorosis, less than one-fourth (23.3%) responded that fluorosis is preventable, while more than three-fourths (77.7%) had no knowledge about fluoride prevention and mitigation programs of government. Also, the attitude of more than two-third of the individuals (70.3%) is negative towards the fluorosis control program. Conclusions: The knowledge, attitude and practices of the study were found to be very low. This suggests that more efforts have to be made at the grass-root level for creating awareness.